Next-generation distillers dried grain as a potential dietary ingredient in dog and cat diets - Smith, Spencer C. (Kansas State University, 2018)
Novel ingredients have been a source of innovation and growth in the pet food market. Further, with rising trends in the humanization of pet food, there has been increased competition between the human food systems and pet food industry for high quality ingredients. Next-generation distillers dried grains (NG-DDG) are a sustainable alternative protein source that show a strong potential for use in companion animal diets. The objectives of this work were to determine the effect of NG-DDG on the extrusion of dry kibbles, the utilization of diets by dogs, the palatability of diets by dogs and cats, and to evaluate the amino acid profile and protein quality through a chick growth assay. Corn gluten meal (CGM) and soybean meal (SBM) were used as standards for comparison. Diets were extruded over 3 days in a complete block design. During extrusion, the NG-DDG kibbles had less radial expansion (P<0.05) compared to the CGM and SBM kibbles (2.62 vs. average 3.10 mm²/mm², respectively). The NG-DDG kibble also required a smaller (P<0.05) mass restriction-valve opening to increase die back-pressure. No other differences in extrusion parameters or kibble texture were observed. Twelve beagle dogs were arranged in a 3x3 replicated Latin Square and were each fed the 3 experimental diets to evaluate digestibility by use of titanium dioxide. Diet produced with CGM was more digestible (P<0.05) in terms of dry matter, organic matter, crude protein, crude fat, and gross energy. Additionally, dogs fed NG-DDG diets had larger (P<0.05) fecal mass than both CGM and SBM (55.65 vs 35.91 and 43.25 g/d, respectively), and a higher (P<0.05) fecal score than dogs fed the CGM diet (3.63 vs. 3.27). Diets were fed to both dogs and cats to assess palatability via a two-bowl test. Dogs had a preference (P<0.05) for CGM over SBM and NG-DDG, but cats showed a preference (P<0.05) for SBM and NG-DDG over CGM. To assess protein quality, one-day old chicks (CobbxCobb; n=120) were fed semi-purified diets containing test ingredients at a 10% crude protein inclusion level, as well as spray dried granulated egg (SDG) and a nitrogen-free basal diet (NEG) to serve as positive and negative controls, respectively. Chicks were arranged in a randomized block design with 6 chicks per pen, 1 pen per battery, and 4 pens per treatment. The protein efficiency ratio (PER) of each treatment was calculated as weight gain (g) per protein intake (g). All experimental treatments had a lower (P<0.05) PER value than the positive control. The PER for NG-DDG and CGM did not differ from each other and had the lowest value of all treatments (P<0.05; average 1.17). In summary, next-generation distillers dried grains can be used to make a similar kibble to CGM and SBM, are similar to SBM in terms of digestibility, and would be an acceptable source of protein in companion animal diets when paired with a supplemental protein source.
Keywords: Pet food; Distillers dried grains; Companion animal; Dog; Nutrition; Extrusion